# Math

Please condense the expression.

1/2ln(x^2+1)-4ln1/2-1/2[ln(x-4)+lnx]

1. 👍 0
2. 👎 0
3. 👁 67

## Similar Questions

1. ### Math

Can someone please condense this expression. I do not know how. 1/2ln(x^2+1)-4ln1/2-1/2[ln(x-4)+lnx]

asked by Joe on May 11, 2010
2. ### Math

Please condense the expression. 1/2ln(x^2+1)-4ln1/2-1/2[ln(x-4)+lnx]

asked by Joe Schmo on May 9, 2010
3. ### Calculus

Evaluate (integral) cot 2x dx. A. 1/2Ln sin 2x+C B. 1/2Ln cos 2x+C C. 1/2Ln sec 2x+C D. 1/2LN csc 2x+C

asked by Cynthia on August 4, 2012
4. ### MAth

1/2ln(x+3)-lnx=0

asked by Meredith on March 27, 2011
5. ### Calculus

yy’-e^x=0, and y=4 when x=0, which means that: y=x-lnx^2+4 y^2=4x^2+3 y=-2x+1/2x^3 y^2=2e^x+14 1/2ln|x^2+4|+6

asked by james on May 10, 2019
6. ### ALGEBRA

Contract the expressions. That is, use the properties of logarithms to write each expression as a single logarithm with a coefficient of 1. text ((a) ) ln\(3\)-2ln\(4\)+ln\(8\) ((b) ln\(3\)-2ln\(4+8\) (c)

asked by Randy on April 16, 2012
7. ### L'Hopital's rule

Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work... =(lnx-(x-1)) / ((x-1)(lnx)) =(lnx-1) / (lnx+ (x+1)/x) This becomes(1/x) / ((1/x)+(1/x^2)) which becomes 1/ (1/x^2) This equals 1/2. I understand the answer has to be -1/2,

asked by Anonymous on October 18, 2011
8. ### calculus

sorry to ask a second question so soon, but i'm just not getting this one. if f(x)= 3x lnx, then f'(x)=? i used f'(x)=3x(D lnx) + D (3x) (lnx) f'(x)=3x (1/x) + 3 (lnx) so... f'(x)=3+3lnx or 3(1+lnx). unfortunately that isn't one

asked by ken on March 2, 2013
9. ### math

integrate dydx=(4sqrt(y)lnx)/x. Check my answer? I got y=((2ln^2(x)+c)/2)^2. Is that right?

asked by Betty on February 24, 2016
10. ### ALGEBRA

Contract the expressions. That is, use the properties of logarithms to write each expression as a single logarithm with a coefficient of 1. text((a) ) ln\(3\)-2ln\(4\)+ln\(8\) text((b) )ln\(3\)-2ln\(4+8\) text((c)

asked by Randy on April 25, 2012

More Similar Questions